Relationship between daily training load and psychometric status of professional soccer players - Moalla, W.; Saifeddin Fessi, M.; Farhat, F.; Nouira, S.; Wong, D. P.; Dupont, G. (Research in Sports Medicine, 2016)
We studied the relationship between daily training load (TL) experienced by professional soccer players and the Hooper questionnaire reflecting their perceived quality of sleep, fatigue, stress and delayed onset muscle soreness. During a 16-week training period, the rating of perceived exertion and duration were collected after each training session, and daily TL was calculated from 14 professional soccer players. The Hooper questionnaire was completed every day before the first training session and the Hooper`s score (HS) was then calculated. The daily TL and HS were 379.9 ± 198.3 AU and 16.2 ± 5.1, respectively. Pearson correlation showed significant relationships (p < 0.01) between TL and perceived fatigue, muscle soreness, sleep and stress. Our findings revealed that the perceived sleep, stress, fatigue and muscle soreness are moderately related to the daily TL in professional soccer players. The Hooper questionnaire is both a simple and useful tool for monitoring perceived wellness and psychometric players` status of professional soccer players.